Macrophages in Atherosclerosis Regression - Barrett, Tessa J (Arteriosclerosis, thrombosis, and vascular biology, 2020)
Macrophages play a central role in the development of atherosclerotic cardiovascular disease (ASCVD), which encompasses coronary artery disease, peripheral artery disease, cerebrovascular disease, and aortic atherosclerosis. In each vascular bed, macrophages contribute to the maintenance of the local inflammatory response, propagate plaque development, and promote thrombosis. These central roles, coupled with their plasticity, makes macrophages attractive therapeutic targets in stemming the development of and stabilizing existing atherosclerosis. In the context of ASCVD, classically activated M1 macrophages initiate and sustain inflammation, and alternatively activated M2 macrophages resolve inflammation. However, this classification is now considered an oversimplification, and a greater understanding of plaque macrophage physiology in ASCVD is required to aid in the development of therapeutics to promote ASCVD regression. Reviewed herein are the macrophage phenotypes and molecular regulators characteristic of ASCVD regression, and the current murine models of ASCVD regression.